2021
DOI: 10.1007/s11845-021-02515-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered mental status is an independent predictor of mortality in hospitalized COVID-19 patients

Abstract: Background/aims Limited data exists on the outcomes of COVID-19 patients presenting with altered mental status (AMS). Hence, we studied the characteristics and outcomes of hospitalized COVID-19 patients who presented with AMS at our hospital in rural southwest Georgia. Methods Data from electronic medical records of all hospitalized COVID-19 patients from March 2, 2020, to June 17, 2020, were analyzed. Patients were divided in 2 groups, those presenting with and without AMS. Primary outcome of interest was in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…However the particularly deliriogenic nature of COVID-19 infection has meant new-onset delirium may be predictive of COVID-19 infection across both primary and secondary care, as it can be the sole symptom of infection in older patients (GOV.UK, 2020; Poloni et al, 2020;Zazzara et al, 2021). Delirium in COVID-19 is associated with poorer outcomes, including a longer requirement for mechanical ventilation, a greater duration of ICU and hospital admission (Garcez et al, 2020;Kenerly et al, 2021;Khan et al, 2020), poorer physical function (Mcloughlin et al, 2020) and increased mortality (Garcez et al, 2020;Kenerly et al, 2021;Marengoni et al, 2020;Poloni et al, 2020;Rebora et al, 2021;Zerah et al, 2021). More widely, delirium is also associated with both an increased future risk of dementia and further neurocognitive decline in surviving patients (Davis et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…However the particularly deliriogenic nature of COVID-19 infection has meant new-onset delirium may be predictive of COVID-19 infection across both primary and secondary care, as it can be the sole symptom of infection in older patients (GOV.UK, 2020; Poloni et al, 2020;Zazzara et al, 2021). Delirium in COVID-19 is associated with poorer outcomes, including a longer requirement for mechanical ventilation, a greater duration of ICU and hospital admission (Garcez et al, 2020;Kenerly et al, 2021;Khan et al, 2020), poorer physical function (Mcloughlin et al, 2020) and increased mortality (Garcez et al, 2020;Kenerly et al, 2021;Marengoni et al, 2020;Poloni et al, 2020;Rebora et al, 2021;Zerah et al, 2021). More widely, delirium is also associated with both an increased future risk of dementia and further neurocognitive decline in surviving patients (Davis et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors did not specifically analyze Levesque’s framework, they nevertheless utilized terms similar or identical to those in the framework. Half of the studies reported the availability (or lack) of healthcare resources due to financial insecurities, a lack of healthcare insurance, education/knowledge gaps, transportation, Internet/phone or telemedicine, cognitive screening, ambulatory care, and so on ([ 26 , 36 , 37 , 38 , 39 ]) (See Table 4 ). These were grouped as materials, financial insecurities, and knowledge gaps.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, at the healthcare system level, organizational inefficiencies, service abilities, and racialized ageism affecting the attitudes and perceptions of healthcare professionals toward older African American adults may diminish healthcare accessibility [ 23 , 24 , 25 ]. Access to services for older African Americans could be worsened due to their more significant residential mobility issues, reduced cell phone access, and transportation limitations [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of a cohort of 710 hospitalized patients found AMS was independently associated with ICU admission and in-hospital mortality. [13] A study of COVID patients presenting to the ED with neurological symptoms found that altered mental status on admission was associated with increased mortality. [14] The association of respiratory symptoms with worse prognoses has also reported by several studies.…”
Section: Discussionmentioning
confidence: 99%